Um ambiente para geração de cenários de testes para linhas de produtos de software sensíveis ao contexto - Santos, Ismayle de Sousa (2013)
A Context-Aware Software Product Line (CASPL) is a product line for developing context-aware applications, which dynamically change their behavior or provide services based on context information. With this kind of line, the productivity can be increased and the development costs of the context-aware application can be cut down. In this scenario, the testing activity needs to deal with the peculiarities of both context-aware applications and the product line development paradigm. Through the complexity involved in testing a CASPL is essential to have methods or tools for supporting this activity, especially with the goal of creating tests from requirements. The aim of this early testing generation is to identify and fix the defects in the early stages of development. Therefore, this work aims to propose an environment for generating test scenarios for a CASPL that takes into account the presence of context information and seeks to maximize the testing reuse. This environment consists of a testing scenario generation method, a template for textual use case specification and a support tool. The method uses as input textual use cases especifications with information about: funcionality, variability, and how the context afect the final products. The environment also has a use case template that supports the use of the method and a tool support, which allows the modeling of use cases according to this template and implements the proposed method. In order to verify the benefits of the environment as a way to testing generation for a Context-Aware Software Product Line, an assessment in the form of controlled experiment is conducted. Based on the collected results, it is observed that: the use of the template makes easy the understanding of a Context-Aware Software Product Line use case; the method favors the creation of a set of tests with higher coverage than a non-systematic testing generation; and the tool is the necessary support for the method